HIV Testing among sexually active Ghanaians: an examination of the rural-urban correlates. - Dey, Nutifafa Eugene Yaw; Owusu Ansah, Kenneth; Norman, Queen Angela; Manukure, Joseph Mfum; Brew, Abigail Boatemaa Kyei; Dey, Enam Amen; Agbadi, Pascal (AIDS & Behavior, 2022)
HIV testing is critical in reducing the risk of HIV transmission. We investigated the rural-urban correlates of HIV testing amongst sexually active Ghanaians using data from the 2017/2018 Ghana Multiple Indicator Cluster Survey Six (GMICS 6). Robust Poisson models (reporting Adjusted Prevalence Ratios (APR) and 95% Confidence Intervals (CIs)) were used to achieve this aim. About 46% of the participants had ever tested for HIV. According to the results, approximately 52% and 39% of urban and rural dwellers, respectively, have undergone HIV testing. HIV knowledge, HIV stigma, gender, age, education, marital status, childbirth history, sexual history, health insurance coverage, media exposure, household wealth, and region of residence were significantly related to HIV testing with observed variations across rural-urban areas. The findings call for the expansion of advocacy efforts towards encouraging HIV testing, targeting sexually active Ghanaians particularly in rural areas.